2013
DOI: 10.1007/s00264-013-2145-5
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review on outcomes of acetabular revisions with highly-porous metals

Abstract: Purpose The purpose of this study was to systematically review the literature and report the clinical and radiographic outcomes of highly-porous acetabular cups in revision settings. Method A literature search of four electronic databases of EMBASE, CINAHL-plus, PubMed, and SCOPUS yielded 25 studies reporting the outcomes of 2,083 revision procedures with highly-porous acetabular components. There was lack of high quality evidence (level I and level II studies) and only two studies with level III evidence, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 63 publications
1
42
0
1
Order By: Relevance
“…The use of the combination of trabecular metal augments and shells allowed us to restore the center of rotation and therefore biomechanics of the hips in the majority of the patients in our series. A high center of rotation of the hip is defined as more than 35 mm above the interteardrop line [2,28] with a systematic review of the use of highly porous metals in acetabular revisions demonstrating correction from a mean of 39 mm to 24 mm [3]. Successful restoration of the hip center was achieved in all but five of the patients in the series.…”
Section: Discussionmentioning
confidence: 99%
“…The use of the combination of trabecular metal augments and shells allowed us to restore the center of rotation and therefore biomechanics of the hips in the majority of the patients in our series. A high center of rotation of the hip is defined as more than 35 mm above the interteardrop line [2,28] with a systematic review of the use of highly porous metals in acetabular revisions demonstrating correction from a mean of 39 mm to 24 mm [3]. Successful restoration of the hip center was achieved in all but five of the patients in the series.…”
Section: Discussionmentioning
confidence: 99%
“…However, revision THA is considered a significantly more complex procedure than routine primary THA for several reasons: (1) extensive surgical approaches are commonly needed for exposure and implant or cement removal [11]; (2) bone defects encountered need to be addresses either with bone grafts or metal augments [12]; (3) modular revision implants are needed to obtain reliable implant fixation [13]. Therefore, revision THA often requires prolonged surgical time with rather large blood loss.…”
Section: Introductionmentioning
confidence: 99%
“…Currently tantalum and titanium are the most frequently used metals in uncemented porous components due to their biologically inert nature and their physical properties that are close to those of cancellous bone [24][25][26][27]. In addition, a recent study by Brüggemann et al has shown little systemic response to tantalum implants, underscoring their safety in joint replacement procedures [28].…”
Section: Discussionmentioning
confidence: 99%